DISFUNCIONALIDAD FAMILIAR Y DEPRESIÓN EN LOS ESTUDIANTES DE SEGUNDO DE BACHILLERATO DE LA UNIDAD EDUCATIVA EMIGDIO ESPARZA MORENO DE LA CIUDAD DE BABAHOYO - MALIZA HERRERA LILIA NAYELLI (2024)
The research aimed to analyze the relationship between family dysfunction and depression in high school students at the Esparza Moreno Educational Unit in the city of Babahoyo. A descriptive- correlational approach was used to explore the characteristics and levels of these variables. The study was non-experimental, meaning that the variables were not manipulated. We employed a quantitative approach and techniques such as Pearson correlation and psychometric tests for data analysis. The sample consisted of 59 students out of a total of 70 students, obtained using the finite population formula. The instruments used were the Family Functioning Questionnaire (FF-SIL) and the Beck Depression Inventory. The results showed a weak positive correlation (correlation coefficient of 0.263) between family dysfunction and depression in these students, indicating a weak positive correlation between the two variables.